Internalization of Character Education Values at the Muhammadiyah Boarding School (MBS) Yogyakarta Elementary School in the Perspective of Al-Ghazali’s Educational Thought. - Assyifa Qori Lhegina; Wasith Achadi; Rosendah Dwi Maulaya (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the process of internalizing Islamic character education values at SD Muhammadiyah Boarding School (MBS) Yogyakarta and examine its alignment with Al-Ghazali's educational thought. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving school leaders, teachers, and students. The findings reveal that the integration of three curricula the National Curriculum, Muhammadiyah (ISMUBA), and Islamic Boarding School forms a holistic system of moral education. The internalization process is carried out through continuous habituation (ta'wīd), spiritual training (riyāḍah al-nafs), moral cultivation (tahdzīb), supervision (murāqabah), teacher modeling (qudwah ḥasanah), and social compassion (iḥsān fī al-mu'āmalah). Implementation at SD MBS includes daily dhuha and zuhur prayers, Qur'an memorization, mahfudzat recitations, fiqh classes, and community service programs. These practices align with Al-Ghazali's view that character education must harmonize intellectual, spiritual, and moral aspects. The study concludes that SD MBS Yogyakarta exemplifies a contextual model of Islamic character education that actualizes Al-Ghazali's moral framework through institutional culture, teacher exemplarity, and parental cooperation.